Expenditure of biological drugs for rheumatoid arthritis treatment in the Brazilian public health system - Mega, Tacila Pires; Silva, Rondineli Mendes da (Revista de Saúde Pública, 2023)
OBJECTIVE: This work aims to analyze the quantity and expenses related to biological drugs used for the treatment of rheumatoid arthritis (RA) in outpatient public care within the Brazilian Unified Health System (SUS). METHODS: It is a cross-sectional descriptive study based on secondary data from a historical series, referring to the purchase, volume, and the number of patients treated with different biological drugs (infliximabe, etanercept, adalimumab, rituximab, abatacept, tocilizumab, golimumab, and certolizumab pegol) for RA treatment in outpatient care from 2012 to 2017. The data were extracted from the SUS Outpatient Information System database-SIA/SUS and included ten drugs used for RA treatment. The study assessed the quantity and expenditure of these drugs, the number of RA patients treated, and the expenditure by RA subtypes. The National Broad Consumer Price Index was used to adjust the expenditures for December 2017. RESULTS: Th e M inistry o f H ealth a llocated approximately 500 m illion t o provide a bout 2 million units of biological drugs for RA patients from 2012 to 2017. The supply of adalimumab 40 mg and etanercept 50 mg accounted for 68.3% of the total expenditure. The subtypes “other rheumatoid arthritis with rheumatoid factor” (ICD-10 M05.8), “rheumatoid arthritis without rheumatoid factor” (ICD-10 M06.0), and “Felty’s syndrome” (M05. 0) represented 84.5% of the total expenditures. The proportion of patients treated with biological drugs increased by 33.0%. There was a significant 83.0% increase in the number of patients using biological drugs compared to the overall number of RA patients treated during the study period. CONCLUSIONS: The results obtained allow us to draw a more recent profile of expenditure on RA treatment and indicate trends in the use of biological drugs for this condition, generating data that can support management decisions in public health policies.